The Effect of L-Citrulline Supplementation on Outcomes of Critically Ill Patients under Mechanical Ventilation; a Double-Blind Randomized Controlled Trial - Asgary, Mohammadreza; Mirghazanfari, Sayid Mahdi; Hazrati, Ebrahim; Hadi, Vahid; Mehri Ardestani, Mojgan; bani Yaghoobi, Faeze; Hadi, Saeid (Archives of Academic Emergency Medicine, 2023)
Introduction: Effective parenteral and enteral amino acid replacement is crucial for critically ill patients with altered amino acid metabolism. This study aimed to assess the effects of l-citrulline supplementation on the clinical and laboratory outcomes in critically patients. Methods: This was a double-blind placebo-controlled randomized clinical trial. 82 critically ill patients who were expected to receive mechanical ventilation for more than 72 hours were selected. The patients were assigned to either a placebo or an intervention group. The patients in the placebo group received 10 gr of microcrystalline cellulose and the ones in the intervention group were given l-citrulline daily for 7 days. Serum levels of fasting blood sugar (FBS), lipid profile, hepatic enzymes, serum electrolytes, urea nitrogen, creatinine, and C-reactive protein (CRP) were evaluated before and after the intervention. Duration of invasive ventilation, intensive care unit (ICU) length of stay, ventilator-free days, and 28-day mortality rate were recorded and compared between groups. Results: Eighty-two patients completed the trial. No statistically significant differences were observed between the two groups in terms of age (p = 0.46), sex (p = 0.49), body mass index (BMI) (p = 0.41), Sequential Organ Failure Assessment (SOFA) Score (p = 0.08), Clinical Pulmonary Infection Score (CPIS) score (p = 0.76), Acute Physiology and Chronic Health Evaluation (APACHE II) score (p = 0.58), risk factors (p = 0.13), ICU stay before randomization (p = 0.32), and reason of admission (p = 0.50) before the intervention. Citrulline group had a notable reduction in FBS (p = 0.04), total cholesterol (TC) (p = 0.02), low density lipoprotein (LDL-C) (p <0.001) and high-sensitivity CRP (hs-CRP) (p <0.001). Also, a significant increase in lactate dehydrogenase (LDH) concentration (p <0.001) was observed in the intervention group at the end of the trial. Total duration of invasive ventilation and the mean SOFA score on 7th day were significantly lower in the citrulline group compared to the control group. Moreover, a significant increase in days alive and ventilator-free days within 28 days after admission was found in the citrulline group at the end of the trial. Also, there were no significant differences between the groups in terms of mortality rate during intervention, serious adverse events, endotracheal intubation, the use of tracheotomy or non-invasive ventilation after extubation, length of ICU stay, ICU-free days at 28 days, and CPIS and APACHE II scores. For mortality, in the citrulline group, there was two deaths compared to eight deaths in the control group. This resulted in an absolute risk reduction (ARR) of 14.05% (95% CI: 0.39–27.71%) and a number needed to treat (NNT) of 7.1 (95% CI: 3.6–29.5), regarding mortality. Conclusions: The results of the present study demonstrated the probable positive effects of citrulline supplementation on lipid profile, hs-CRP levels, duration of invasive ventilation, and SOFA score. Also, l-citrulline consumption may increase the probability of survival without mechanical ventilation.